Pengaruh Komunikasi, Reward Dan Semangat Kerja Terhadap Kinerja Pegawai CV. Sari Bhuana Singaraja - Riana Dewi Kartika (ARTHA SATYA DHARMA, 2021)
The research results in this study stated that the parameter coefficient value of Communication on Employee Performance was positive and significant where the coefficient value was 0.192 and t value was 7.085 which turned out to be greater than t table 1.96, Reward to Employee Performance was positive and significant where the value the coefficient is 0.522 and the value of t is 9.786 which turns out to be greater than t table 1.96, the morale of Employee Performance is positive and significant where the coefficient value is 0.319 and the value of t is 6.103 which turns out to be greater than t table 1.96. So it can be concluded that the value of the positive coefficient and the value of t is greater than t table then it can be stated that the results of this study are significant so the first hypothesis to the fifth is accepted.